Adiposity rebound and cardiometabolic health in childhood: results from the Generation XXI birth cohort - Fonseca, MJ (2021)
Background: We aimed to evaluate the association of adiposity rebound (AR) timing on cardiometabolic health in childhood. Methods: Participants were part of the Generation XXI birth cohort, enrolled in 2005/2006 in Porto. All measurements of the child's weight and height performed by health professionals as part of routine healthcare were collected. Individual body mass index (BMI) curves were fitted for 3372 children, using mixed-effects models with smooth spline functions for age and random effects. The AR was categorized into very early (<42 months), early (42-59 months), normal (60-83 months) and late (≥84 months). At age 10 years, cardiometabolic traits were assessed and age- and sex-specific z-scores were generated. Adjusted regression coefficients and 95% confidence intervals [β (95% CI)] were computed. Results: The mean age at AR was 61.9 months (standard deviations 15.7). Compared with children with normal AR, children with very early or early AR had higher z-scores for BMI [β = 0.40 (95% CI: 0.28; 0.53); β = 0.21 (95% CI: 0.12; 0.30)], waist circumference [β = 0.33 (95% CI: 0.23; 0.43); β = 0.18 (95% CI: 0.10; 0.25)], waist-height ratio [β = 0.34 (95% CI: 0.24; 0.44); β = 0.14 (95% CI: 0.07; 0.22)], fat mass index [β = 0.24 (95% CI: 0.15; 0.33); β = 0.14 (95% CI: 0.08; 0.21)], fat-free mass index [β = 0.25 (95% CI: 0.14; 0.35); β = 0.11 (95% CI: 0.03; 0.19)], systolic blood pressure [β = 0.10 (95% CI: 0.01; 0.20); β = 0.08 (95% CI: 0.01; 0.15)], insulin [β = 0.16 (95% CI: 0.04; 0.29); β = 0.10 (95% CI: 0.01; 0.19)], HOMA-IR [β = 0.17 (95% CI: 0.04; 0.29); β = 0.10 (95% CI: 0.03; 0.19)] and C-reactive protein [β = 0.14 (95% CI: 0.02; 0.26); β = 0.10 (95% CI: 0.01; 0.19)]. Children with very early AR also had worse levels of diastolic blood pressure [β = 0.09 (95% CI: 0.02; 0.16)], triglycerides [β = 0.21 (95% CI: 0.08; 0.34)] and high-density lipoprotein cholesterol [β=-0.18 (95% CI: -0.31; -0.04)]. When analysed continuously, each additional month of age at the AR was associated with healthier cardiometabolic traits. Conclusion: The earlier the AR, the worse the cardiometabolic health in late childhood, which was consistently shown across a wide range of outcomes and in the categorical and continuous approach.